The exam anxiety among vocational school students in professional placement based on gender differences - Handayuni, Tyesa Sri; Ifdil, Ifdil; Putri, Yola Eka (Universitas Negeri Padang, 2020)
This study aims to analyze exam anxiety among vocational school students in professional placement based on gender. This is a quantitative research that uses descriptive and comparative methods and a sample of 115 individuals selected through proportional random sampling technique. Data is obtained using an instrument of exam anxiety and were analyzed descriptively by determining mean, standard deviation, and percentage. To determine the difference in anxiety among vocational school students, the t-test technique with analyzed Independent Samples Test was used. The results showed that exam anxiety was generally in the low and high categories in male and female students, respectively. Also, there was a significant difference between students in the professional placement of male and female students.